Building climate resilience: Agroecology in the dry corridor - Muller, Lolita; Steward, Peter; Rosenstock, Todd (2025)
KEY MESSAGES - The integration of agroecological practices stands out as a promising strategy to enhance resilience against climate hazards. - Agroecological practices such as mulch, crop residues, shaded trees and living barriers increase climate resilience by increasing soil moisture or decreasing soil temperature and erosion. - While agroecological practices may require initial investments, they are not an economic burden for smallholders. - This analysis leads to several actionable recommendations for policymakers and stakeholders including investing in farmer education on agroecology and providing financial support for the initial transition period.